2007
DOI: 10.1097/01.brs.0000251750.20508.84
|View full text |Cite
|
Sign up to set email alerts
|

Cauda Equina Syndrome

Abstract: In our series, the symptom duration before operation and the speed of onset do not affect the outcome more than 2 years after surgery. Based on the SF-36, ODI, and Low Back Outcome Scores, patients who have had CES do not return to a normal status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(39 citation statements)
references
References 49 publications
3
32
3
1
Order By: Relevance
“…The study of McCarthy et al evaluated outcome of both micturition, defecation and sexual function in a cohort of 42 CES patients with a shorter follow up time than the current study (mean 5 years, minimum 2.1 years), demonstrating similar rates of dysfunction of micturition (36%), but slightly higher rates of dysfunction of defecation (60%) and sexual function (57%). [28] The higher rates of defecation and sexual dysfunction in the cohort of McCarthy et al compared to that of the presented cohort, might suggest that improvement is still possible several years post-surgery.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The study of McCarthy et al evaluated outcome of both micturition, defecation and sexual function in a cohort of 42 CES patients with a shorter follow up time than the current study (mean 5 years, minimum 2.1 years), demonstrating similar rates of dysfunction of micturition (36%), but slightly higher rates of dysfunction of defecation (60%) and sexual function (57%). [28] The higher rates of defecation and sexual dysfunction in the cohort of McCarthy et al compared to that of the presented cohort, might suggest that improvement is still possible several years post-surgery.…”
Section: Discussionmentioning
confidence: 76%
“…[28] With regard to the first finding: in our regression analysis, no differentiation was made between urinary incontinence and other micturition problems at follow up. Evaluating the outcome for micturition in our study closer, displays that the 6 patients with urinary incontinence at long term follow up, were all female; of the remaining 8 patients with micturition problems but without incontinence, 3 were female and 5 were male.…”
Section: Discussionmentioning
confidence: 99%
“…2). Selection procedure and subsequent citation tracking resulted in 16 reports on 15 different studies that met all criteria [5,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. One study was reported in two publications [19,20].…”
Section: Characteristics Of Included Studies and Risk Of Biasmentioning
confidence: 99%
“…Except for three patients who were treated conservatively [5,17,24], all patients underwent surgery. Four authors did not give exact information about type of surgery [5,[22][23][24]. Outcome was descriptive in eight studies [13,14,16,17,21,22,26,27], graded in six studies [5,15,18,20,23,25] and both urodynamic and descriptive in one study [24].…”
Section: Characteristics Of Included Studies and Risk Of Biasmentioning
confidence: 99%
“…Urgent surgical decompression, 17 , 18 even though the exact time limit for the surgery is debated by different authors, 12 , 14 continues to be the most effective treatment. This is the only safe way of preventing the progression of the lesion and its permanent deficits 19 …”
Section: Discussionmentioning
confidence: 99%